Czym była, a czym stała się w renesansie Batrachomyomachia - Zbądzki, Jakub (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Zbądzki Jakub, Czym była, a czym stała się w renesansie Batrachomyomachia (What the Batrachomyomachia was, and what it became in the Renaissance). The paper presents the Batrachomyomachia as an example of hellenistic poetry and discusses its reception in the Renaissance, when it became very popular, but all its complexity was lost.